Removal of chromium (VI) with Aliquat 336 impregnated in Amberlite XAD-16. I. batch mode sorption studies - Sadikin, Aziatul Niza; Ab. Muis, Zarina; Saha, Basu (Penerbit UTM Press, 2007)
This work investigates the removal of chromium (VI) from aqueous solutions using solvent impregnated resin (SIR). The solvent impregnated resin was formed by impregnating Amberlite XAD-16 resin with Aliquat 336 extractant. Solvent impregnated resins were prepared in three different concentrations; 0.5, 1.0 and 2.0 grams Aliquat 336 per gram XAD-16. The solvent impregnated resin was formed using the wet method. The effect of pH on the sorption of chromium (VI) ions was investigated; equilibrium experiments were carried out with the different concentrations of solvent impregnated resin to test the sorption capacity. It was found that the sorption of chromium (VI) was most effective at pH 6. It was found that 90% removal was achieved under optimal conditions. The adsorption capasity for chromium was found to be 0.47, 0.56 and 0.63 mmol/g for 0.5, 1.0 and 2.0 g/g, respectively